1997
DOI: 10.1159/000106632
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebellum in Alzheimer's Disease

Abstract: The cerebellum is a relatively neglected area of the Alzheimer''s disease (AD) brain, probably because it was formerly thought to be spared by the disease. However, a number of pathological changes have now been revealed in the AD cerebellum, principally by immunocytochemical studies, including widespread deposits of diffuse amyloid, ubiquitin-immunoreactive dystrophic neurites, and increased microglia, but tau-immunoreactive neurofibrillary tangles have not been seen. Although the observed changes may be mere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
95
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 58 publications
11
95
0
1
Order By: Relevance
“…One explanation for our finding is that the signal from any potential 18 F-florbetaben binding in the cerebellum will be small, is likely to fall within the margins of error in PET signal measurement, and will therefore not be detectable. Another possible explanation may be the morphologic and immunocytochemical differences between the neuropathologic lesions of AD in the cerebral cortex and cerebellum (11). As expected, the amount of cerebellar Ab deposition assessed pathologically correlated positively with cortical SUVRs in the full sample of patients; subjects without Ab deposition in the cerebral cortex did not show Ab deposition in the cerebellum, and the higher the amount of cerebellar Ab deposition was, the higher was the cerebral cortical SUVR.…”
Section: Discussionsupporting
confidence: 58%
“…One explanation for our finding is that the signal from any potential 18 F-florbetaben binding in the cerebellum will be small, is likely to fall within the margins of error in PET signal measurement, and will therefore not be detectable. Another possible explanation may be the morphologic and immunocytochemical differences between the neuropathologic lesions of AD in the cerebral cortex and cerebellum (11). As expected, the amount of cerebellar Ab deposition assessed pathologically correlated positively with cortical SUVRs in the full sample of patients; subjects without Ab deposition in the cerebral cortex did not show Ab deposition in the cerebellum, and the higher the amount of cerebellar Ab deposition was, the higher was the cerebral cortical SUVR.…”
Section: Discussionsupporting
confidence: 58%
“…Last, we found that abnormal tau hyperphosphorylation occurred in the cerebral cortex and hippocampus but to a lesser extent in the cerebellum. In AD, NFTs are observed in the hippocampus and neocortex but not the cerebellum (Larner, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, the cerebellum is not affected by reduced metabolism and is devoid of NFTs (Kushner et al, 1987;Larner, 1997). From these evidences, we hypothesized that in vivo alterations in glucose metabolism might be a potential cause of tau hyperphosphorylation.…”
Section: Introductionmentioning
confidence: 88%
“…Cerebellar granule neurons are a suitable model because the cells are non-transformed, they can be efficiently transfected with non-viral vectors, and they are highly dependent upon insulin and IGF signaling for function. In addition, the cerebellar cortex is a target of neurodegeneration in various diseases including, AD (Cole, Neal et al 1993;Ishii, Sasaki et al 1997;Larner 1997;Wegiel, Wisniewski et al 1999). Gaithersburg, MD).…”
Section: Methodsmentioning
confidence: 99%